Genetic Variation Within the HLA-DRA1 Gene Modulates Susceptibility to Type 1 Diabetes in HLA-DR3 Homozygotes - Aydemir, Özkan; Noble, Janelle A; Bailey, Jeffrey A; Lernmark, Åke; Marsh, Patrick; Andersson Svärd, Agnes; Bearoff, Frank; Blankenhorn, Elizabeth P; Mordes, John P (Diabetes (New York, N.Y.), 2019)
Type 1 diabetes (T1D) involves the interaction of multiple gene variants, environmental factors, and immunoregulatory dysfunction. Major T1D genetic risk loci encode HLA-DR and -DQ. Genetic heterogeneity and linkage disequilibrium in the highly polymorphic HLA region confound attempts to identify additional T1D susceptibility loci. To minimize HLA heterogeneity, T1D patients ( = 365) and control subjects ( = 668) homozygous for the HLA-DR3 high-risk haplotype were selected from multiple large T1D studies and examined to identify new T1D susceptibility loci using molecular inversion probe sequencing technology. We report that risk for T1D in HLA-DR3 homozygotes is increased significantly by a previously unreported haplotype of three single nucleotide polymorphisms (SNPs) within the first intron of The homozygous risk haplotype has an odds ratio of 4.65 relative to the protective homozygous haplotype in our sample. Individually, these SNPs reportedly function as "expression quantitative trait loci," modulating and - expression. From our analysis of available data, we conclude that the tri-SNP haplotype within may modulate class II expression, suggesting that increased T1D risk could be attributable to regulated expression of class II genes. These findings could help clarify the role of HLA in T1D susceptibility and improve diabetes risk assessment, particularly in high-risk HLA-DR3 homozygous individuals.